Functional assessment of variants associated with Wolfram syndrome. (10th October 2019) - Riachi, Melissa; Yilmaz, Sebahat; Kurnaz, Erdal; Aycan, Zehra; Çetinkaya, Semra; Tranebjærg, Lisbeth; Rendtorff, Nanna Dahl; Bitner-Glindzicz, Maria; Bockenhauer, Detlef; Hussain, Khalid
Abstract: Wolfram syndrome (WS) is a heterogeneous multisystem neurodegenerative disorder with two allelic variations in addition to a separate subtype known as WS type 2. The wide phenotypic spectrum of WS includes diabetes mellitus and optic atrophy which is often accompanied by diabetes insipidus, deafness, urological and neurological complications in combination or in isolation. To date, the understanding of the genotype-phenotype relationship in this complex syndrome remains poorly understood. In this study, we identified and explored the functionality of rare and novel variants in the two causative WS genes WFS1 and CISD2 by assessing the effects of the mutations on the encoded proteins Wolframin and ERIS, in a cohort of 12 patients with autosomal recessive WS, dominant WS and WS type 2. The identified pathogenic variants included missense changes, frameshift deletions and insertions in WFS1 and an exonic deletion in CISD2 which all altered the respective encoded protein in a manner that did not correlate to the phenome previously described. These observations suggest the lack of genotype-phenotype correlation in this complex syndrome and the need to explore other molecular genetic mechanisms. Additionally, our findings highlight the importance of functionally assessing variants for their pathogenicity to tackle the problem of increasing variants of unknown significance in the public genetic databases.